2013
DOI: 10.1080/17439760.2012.758305
|View full text |Cite
|
Sign up to set email alerts
|

Self- and peer-rated character strengths: How do they relate to satisfaction with life and orientations to happiness?

Abstract: This paper addresses the question as to whether previously reported findings on a positive relation between character strengths, satisfaction with life, and orientations to happiness (OTH) can be replicated for peer ratings of character strengths. A sample of 334 Swiss adults completed questionnaires and collected informant ratings by 634 peers. Selfand peer ratings converged well and suggest that, primarily: the strengths of hope, zest, and curiosity -but also gratitude and love -play key roles in the interpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
92
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 53 publications
(49 reference statements)
11
92
1
9
Order By: Relevance
“…Hope, together with love, gratitude, curiosity and zest are the character strengths whose levels share the strongest relationship to our subjective well-being (Park, Peterson & Seligman, 2004;Peterson, Ruch, Beerman, Park, & Seligman, 2007;Buschor, Proyer & Ruch, 2013). Subjective well-being is a holistic judgement based on high scores in positive emotion and satisfaction with our life, and lower scores on our negative emotion .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hope, together with love, gratitude, curiosity and zest are the character strengths whose levels share the strongest relationship to our subjective well-being (Park, Peterson & Seligman, 2004;Peterson, Ruch, Beerman, Park, & Seligman, 2007;Buschor, Proyer & Ruch, 2013). Subjective well-being is a holistic judgement based on high scores in positive emotion and satisfaction with our life, and lower scores on our negative emotion .…”
Section: Resultsmentioning
confidence: 99%
“…Many of the measurements for character strengths and its correlates rely on self-report so do these findings hold up, then, in peer-rated reports? A recent study of Swiss adults, including informant ratings, found that hope, zest, love, gratitude and curiosity play key roles in life satisfaction (Buschor, Proyer & Ruch, 2013). The peer ratings of strengths related positively with the individual's endorsement of a pleasurable, engaged and meaningful life.…”
Section: Strengths Of Character and Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this direction, research so far has shown contradicting results, although several studies show that the endorsement of character strengths, such as hope, zest or love, is significantly related to a higher degree of well-being and Positive Affect (PA) (e.g., Buschor et al, 2013;. At the same time, some authors have found that hope, zest, love, social intelligence, perseverance, and those strenghts related to the use and acquisition of knowledge seem to be the most related character strengths to PA while other authors find that all strengths result significantly and directly related to PA (Azañedo, 2014;.…”
Section: Introductionmentioning
confidence: 96%
“…C. Peterson and M. Seligman (Peterson & Seligman, 2004) refer to the moral character of humor and its role in "making the human condition more bearable by drawing attention to its contradictions, by sustaining good cheer in the face of despair, by building social bonds, and by lubricating social interaction" (p. 530). Humor is considered to be a form of manifestation of the positive personality functioning and a sign of mental health (Buschor, Proyer & Ruch, 2013;Niemiec, 2013).…”
Section: Introductionmentioning
confidence: 99%